2019
DOI: 10.1038/s41467-018-08138-1
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal nano-perforator of viral membrane trapping viral RNAs in the endosome

Abstract: Membrane-disrupting agents that selectively target virus versus host membranes could potentially inhibit a broad-spectrum of enveloped viruses, but currently such antivirals are lacking. Here, we develop a nanodisc incorporated with a decoy virus receptor that inhibits virus infection. Mechanistically, nanodiscs carrying the viral receptor sialic acid bind to influenza virions and are co-endocytosed into host cells. At low pH in the endosome, the nanodiscs rupture the viral envelope, trapping viral RNAs inside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 43 publications
(52 reference statements)
1
29
0
Order By: Relevance
“…The peptide bound specifically to HIV-1 by interacting with gp41 and was shown to prevent viral replication in a dose-dependent manner. In addition, phospholipids can be rearranged into a planar nanostructure known as nanodiscs [ 280 ]. When conjugated with sialic acid, nanodiscs have been able to selectively bind to H1N1, H3N2, and H5N2 viruses and neutralize their infectivity in a plaque assay.…”
Section: Nanotechnology Interventionsmentioning
confidence: 99%
“…The peptide bound specifically to HIV-1 by interacting with gp41 and was shown to prevent viral replication in a dose-dependent manner. In addition, phospholipids can be rearranged into a planar nanostructure known as nanodiscs [ 280 ]. When conjugated with sialic acid, nanodiscs have been able to selectively bind to H1N1, H3N2, and H5N2 viruses and neutralize their infectivity in a plaque assay.…”
Section: Nanotechnology Interventionsmentioning
confidence: 99%
“…After 4, 6, and 8 h, the cells were washed thrice with PBS for 5 min and fixed in 100% methanol. Influenza A virus particles were detected though immunofluorescence of NA as previously reported ( 17 ). Anti-influenza A virus NP antibody and Alexa Fluor 647-labeled goat-anti mouse IgG H&L antibody (Abcam, Cambridge, MA, USA) were used.…”
Section: Methodsmentioning
confidence: 80%
“…The virucidal effect was the strongest activity observed for RcP which might suggest that an anti-CHIKV mechanism of action for this complex might be related to a direct action on the viral particle envelope. Previous studies have shown that the virucidal effect of several compounds is closely related to an action on the virus envelope (Tang et al, 1990;Schuhmacher et al, 2003;Carravilla et al, 2017;Kong et al, 2019;Russo et al, 2019). This suggests the existence of interactions between CHIKV envelope glycoproteins and RcP.…”
Section: Discussionmentioning
confidence: 93%